Antioxidant properties of leaves extracts of acanthaceae species - Al-Hakimi, Anisa Saeed; Saeed, Seham; Omar, Naser; Abdul Latiff (Penerbit Universiti Kebangsaan Malaysia, 2023)
The objective of this study is to determine the antioxidant properties of leaves extracts of 24 Acanthaceae species: Asystasia guttata, Ballochia amoena, Barleria aculeata, B. orbicularis, B. parviflora, B. prionitis, B. ventricosa, Blepharis cayaniense, B. maderaspatensis, Crossandra, johanninae, Dicliptera effusa, D. paniculata, D. verticillata, Ecbolium gymnostachyum, Hypoestes pubescens, H. triflora, Justicia caerulea, J. heterocarpa, J. odora, Megalochalmyas violacea, Phaulopsis imbricata, Trichocalyx orbicular, Ruellia grandiflora and R. paulayana. The radical scavenging activities of 2,2 diphenyl-1-picrylhydrazyl, ferric-reducing antioxidant power, and total phenolic compounds of species were determined using the Folin-Ciocalteau reagent. Blepharis cayaniense has the highest phenolic compounds (995.5 mg of gallic acid per g of sample) while Hypoestes pubescens, and Ruellia paulayana (10 mg/mL gallic acid equivalent) have the lowest concentration of phenolic acid but less radical scavenging activities (DPPH) and reducing ferric power. Only Trichocalyx orbiculatus has the highest concentration in phenolic content, radical-scavenging activities, and reducing power. Interestingly, the antioxidant activities of different Acanthaceae species exhibit unique medicinal properties.